A Review of The Suitability of Mangrove Agro-ecotourism Areas in Perupuk Village, Batubara Regency, North Sumatra Province - Uswatul Hasan; Siti Mardiana; Syahbudin Hasibuan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This study aimed to measure the suitability of mangrove ecosystems in Perupuk village, Batubara district as an ecotourism area. Several ecological parameters were used as a basis for considering suitability including mangrove type, thickness, and density. In addition, biota diversity and tidal height were also observed. Mangrove observations were carried out using the 10 x 10 metre quadratic transect method as many as 20 pieces were let on the shoreline area toward, land. The results showed that this area was only overgrown with Avicennia marina with a thickness of 203.7 meters, and a density of 2100 Ind/ha. There are 31 species of biota associated with mangrove ecosystems consisting of 3 bivalve species, 1 gastropod, 6 fish, 16 birds, 2 crustaceans, 2 arthropods, and 1 mammal. The results of the ecotourism suitability index analysis show that this area is very suitable for mangrove ecotourism sites with a suitability value of 73.75%